Possible sense effects on reading about biotechnology in a textbook (Research, Society and Development, 2020)
Considering that Biotechnology has many controversies, in this research we try to understand how biotechnological themes appear in a textbook. For this, we analyze how written structure and images, present in a chapter of a high school biology textbook, can contribute to the production of meanings about biotechnological products and the controversies associated with them. As a theoretical and methodological support, we joined the Pecheutian Discourse Analysis, mainly in productions by Eni Orlandi. We start from the relation between form and content, considering some principles and notions, such as power relations, anticipation mechanisms and discursive formations, in order to understand the production of meanings from the image-text interaction. Based on the stated assumptions, we point out that these images have a dependence on the text so that they can join a biotechnological discourse, which can go against the production of meanings expected from the teaching point of view. We also point out that it is from a game between discursive typologies (pedagogical, scientific and daily discourse) that the text of the textbook is constructed.